Microglanis nigrolineatus, a new species from northwestern Argentina (Ostariophysi: Pseudopimelodidae) - Teran, Guillermo Enrique (2016)
Microglanis nigrolineatus, new species, is described from streams of Bermejo River basin, northwestern Argentina. It is distinguished from all congeners by a combination of characters including a unique coloration pattern: a thin dark line that runs along middle body from vertical line through dorsal-fin origin to end of adipose fin, delimiting two dark-brown areas ending in a dark blotch crossing entire body depth just anterior to caudal-fin origin and dorsal region of head uniformly dark, lacking a paler area on nuchal region. Also, thorn serrae on anterior margin of pectoral-fin spine are short. This is the first species of Microglanis described from Argentina.